Solidity effect on corner separation and its control in a high-speed low aspect ratio compressor cascade. (July 2018) - Tang, Yumeng; Liu, Yangwei; Lu, Lipeng
Highlights: Solidity effect on the evolution of 3D corner separation is investigated in a high-speed low aspect ratio compressor cascade. A new type of separation termed blade suction surface stall, is proposed, on occasion of negative S indicator values. The relative position between the initial separation point and the blade suction surface throat position is linked with loss and associated to separation form. The newly proposed blade suction surface stall occurs when the initial separation point moves ahead of the suction surface throat position simultaneously with the confluence of the two end side separation zones in the blade middle aft. The blade end jet control scheme is demonstrated to verify a promising perspective of the passive blade end slot control strategy for mitigating 3D corner separation. Abstract: Three-dimensional (3D) corner separation flow is the main source of losses and blockages in compressors, and it is vital to the compressor performance. This paper investigates the solidity effect on the evolution of 3D corner separation in a high-speed low aspect ratio cascade. The effect of solidity on the corner separation mechanism is analysed in detail and the relative position relationship between the separation point and the blade suction surface throat position, is found to be critical to the evolution of the 3D corner separation. A new type of separation termed blade suction surface stall, is proposed, on occasion of negative S indicator values. The formation mechanism for this newly proposed stall is investigated in detail, in association with the solidity variation. This kind of stall occurs when the onset of the separation point moves ahead of the throat point on the blade suction surface and simultaneously with the confluence of the two end side separation zones in the blade middle. Based on the detachment mechanisms for the evolution of the 3D corner separation, a blade end jet control scheme is conceived to mitigate the 3D corner separation. The results indicate its benefit range and verify the potential of implementing it incorporated with solidity reduction. Graphical abstract :